Far Right times in Argentina: Social and Labor Conflicts in the Beginnings of Milei’s government - Marticorena, Clara (2024)
The article aims to describe and analyze the balance of power between workers and popular classes and the State in Argentina, since a the recently elected far-right government of Javier Miei took office